Rethinking Muslim Consumption: Israf and Tabdzir as Ethical Boundaries in Everyday Economic Behavior - Mochammad Arif Budiman (Indonesian Journal of Applied Accounting and Finance, 2025)
In recent decades, consumption patterns in Muslim societies have increasingly reflected global consumer culture characterized by excess and waste. This trend contradicts Islamic ethical teachings that emphasize moderation and responsibility in economic behavior. This study aims to examine israf (excessiveness) and tabdzir (wastefulness) as ethical boundaries that regulate everyday Muslim consumption. Using a qualitative conceptual approach based on Qur’anic teachings and contemporary Islamic economics literature, this paper analyzes how these concepts function as moral constraints in economic decision-making. The findings show that israf represents consumption beyond reasonable limits, while tabdzir refers to wasteful and unproductive use of resources. Rather than being treated as neutral behavioral categories, both concepts serve as ethical limits that prevent deviation from moderation (wasatiyyah). This study contributes to Islamic economic discourse by providing a simplified framework of ethical bounded consumption that aligns with sustainability and responsible resource use.